Performance evaluation of dual diversity cognitive ad-hoc routing protocol (D2CARP) on primary user (PU) activation time: a simulation approach / Rafiza Ruslan and Nur Maisarah Ab Rahman - Ruslan, Rafiza; Ab Rahman, Nur Maisarah (UiTM Cawangan Perlis, 2017)
Cognitive Radio (CR) is known to solve spectrum scarcity that intent to improve spectrum utilization. In CR, secondary user (SU); also known as cognitive user need to ensure its transmission will not interfere primary user (PU) link. Link breakages among secondary users are due to PU activity that causing the degradation of network performance. Over the past decades, many routing protocol were developed for CR network. This paper focusses only on Dual Diversity Cognitive Ad-hoc Routing Protocol (D2CARP) that jointly exploits path and spectrum diversity to provide multi-path and multi-channel solutions to SU. SU can switch to another channel or path if the current path breaks or the channel becomes unavailable. This project aims to provide a comparison network performance in different distributions running under the same routing protocol. The objectives of this project are to imitate a cognitive radio ad-hoc network using Network Simulator 2 (NS-2) and to create two scenarios in Exponential and Uniform distributions. The performance was analysed based on the percentage of packet drop, average packet delay and throughput. The results in both distributions show a slight difference. From the research, it can be concluded that D2CARP is able to work well under random PU activation time as long as the SU number does not exceed the network capacity.